Implementing radical cure diagnostics for malaria: user perspectives on G6PD testing in Bangladesh - Engel, N; Ghergu, C; Matin, MA; Kibria, MG; Thriemer, K; Price, RN; Ding, XC; Howes, RE; Ley, B; Incardona, S; Alam, MS (BioMed Central, 2021)
Background The radical cure of Plasmodium vivax requires treatment with an 8-aminoquinoline drug, such as primaquine and tafenoquine, to eradicate liver hypnozoite stages, which can reactivate to cause relapsing infections. Safe treatment regimens require prior screening of patients for glucose-6-phosphate dehydrogenase (G6PD) deficiency to avoid potential life-threatening drug induced haemolysis. Testing is rarely available in malaria endemic countries, but will be needed to support routine use of radical cure. This study investigates end-user perspectives in Bangladesh on the introduction of a quantitative G6PD test (SD Biosensor STANDARD™ G6PD analyser) to support malaria elimination. Methods The perspectives of users on the SD Biosensor test were analysed using semi-structured interviews and focus group discussions with health care providers and malaria programme officers in Bangladesh. Key emerging themes regarding the feasibility of introducing this test into routine practice, including perceived barriers, were analysed. Results In total 63 participants were interviewed. Participants emphasized the life-saving potential of the biosensor, but raised concerns including the impact of limited staff time, high workload and some technical aspects of the device. Participants highlighted that there are both too few and too many P. vivax patients to implement G6PD testing owing to challenges of funding, workload and complex testing infrastructure. Implementing the biosensor would require flexibility and improvisation to deal with remote sites, overcoming a low index of suspicion and mutual interplay of declining patient numbers and reluctance to test. This approach would generate new forms of evidence to justify introduction in policy and carefully consider questions of deployment given declining patient numbers. Conclusions The results of the study show that, in an elimination context, the importance of malaria needs to be maintained for both policy makers and the affected communities, in this case by ensuring P. vivax, PQ treatment, and G6PD deficiency remain visible. Availability of new technologies, such as the biosensor, will fuel ongoing debates about priorities for allocating resources that must be adapted to a constantly evolving target. Technical and logistical concerns regarding the biosensor should be addressed by future product designs, adequate training, strengthened supply chains, and careful planning of communication, advocacy and staff interactions at all health system levels.